The Influence of the Application of the Science, Technology, Engineering, and Mathematics (STEM) Approach Assisted by Assemblr Edu on Improving the Scientific Literacy Skills of Elementary School Students - Febriyani, Frida; Nuraeni, Fitri; Iskandar, Sofyan (Journal of Digital Learning and Education, 2024)
This study is motivated by the low level of scientific literacy skills among students. The objective of this research is to measure the improvement and determine the influence of learning using the STEM approach assisted by Assemblr Edu, compared to learning that uses the Scientific approach. The research method employed is Quasi-Experimental with a non-equivalent control group design and purposive sampling technique. The research sample consists of 30 students in both the experimental and control groups. The instruments used in this study include a scientific literacy skills test and non-test instruments such as student worksheets and documentation. Data analysis results show that learning with the STEM approach assisted by Assemblr Edu has a significant influence on students' scientific literacy skills, with an effect size of 57.6%. Based on these results, it can be concluded that the STEM approach assisted by Assemblr Edu has a significant correlation and positive impact on scientific literacy skills. Learning through the application of the STEM approach assisted by Assemblr Edu demonstrates an influence of 57.6%, indicating that the implementation of the STEM approach assisted by Assemblr Edu impacts the improvement of students' scientific literacy skills.